Development Prospects of the Brand of Tomsk - KEKSEL, Olga Sergeevna; IVCHIK, Alena Aleksandrovna; SHTANKO, Marina Aleksandrovna; AZAROVA, Svetlana Valerievna; SUKHUSHINA, Elena Valerievna (Journal of Environmental Management and Tourism, 2016)
The importance of territory branding is connected with the necessity of elaboration of new strategic approaches to brand creation of a country, a region, a city, along with the restatement of existent types of territory positioning in a view of harden competition between the cities for attracting of investments, opportunities and tourists. Creation of a strong, sustainable brand which can represent the city not only in Russia, but also abroad becomes topical. The modern reality is such that economic and demographic crisis reduces the amount of available financial and human capital assets. Under such conditions, the territories compete severely for any available resources. The winner of the competition is the one which can adapt to the changing situation and apply maximum tools for it. The territory branding is the main instrument for visitors’ attraction and most significantly for investors’ attraction as well as it is an important way of people’s loyalty forming. An increasing number of countries, regions and cities use territory branding. This way of attractiveness forming is especially developed abroad, but Russian cities and regions are mastering actively the territory branding. They don’t always succeed. The efficiency of this marketing instrument depends on many factors. The main issue the brand developers face is that they are mistaken in the understanding of territory brand as a beautiful image for tourist attraction. Tomsk is one of those cities which have enough peculiarities to be distinguished from others by means of creation of a strong and sustainable brand for representing the city outside it.
Keywords: brand; city branding; territory branding; marketing